DRUM‐PD: The Use of a Drum Circle to Improve the Symptoms and Signs of Parkinson's Disease (PD). Issue 3 (21st December 2015) - Pantelyat, Alexander; Syres, Candace; Reichwein, Suzanne; Willis, Allison
Abstract: Background: Physical therapy can improve motor function in patients with Parkinson's disease (PD). Music performance may be used to improve motor skills by rhythmic entrainment. Drumming has long been a part of traditional healing rituals worldwide and is increasingly being utilized as a therapeutic strategy. Methods: This pilot controlled prospective and cohort trial assessed feasibility and effects of twice‐weekly group West African drum circle classes for 6 weeks on PD patients' quality of life, symptoms, motor findings, cognition, and mood. Ten patients with PD were recruited into the drum circle group. Ten patients with PD were matched pairwise to each of the drum circle participants and enrolled in a no‐intervention control group. Both groups completed the PD‐specific Parkinson Disease Questionnaire (PDQ)‐39 quality of life assessment and the Geriatric Depression Scale and underwent motor and cognitive assessments by a rater blinded to group at baseline, 6 weeks, and 12 weeks. Results: Drummers had significantly improved PDQ‐39 scores from baseline to 6 weeks (−5.8; P = 0.042), whereas the control group's scores were unchanged. Walking performance was significantly faster at baseline for controls; after 6 weeks of drumming, this difference was no longer significant and remained nonsignificant at 12 weeks. The drummers trended ( P = 0.069) toward improvement in walking from baseline to 12 weeks. Other outcomes did not significantly change from baseline to 6 or 12 weeks. Conclusions: Drum circle classes significantly and reversibly improved quality of life in patients with PD. This pilot trial's findings merit larger controlled investigations comparing drumming classes to established interventions in PD, such as physical therapy.